2007
DOI: 10.1200/jco.2006.08.8021
|View full text |Cite
|
Sign up to set email alerts
|

FCGR2A and FCGR3A Polymorphisms Associated With Clinical Outcome of Epidermal Growth Factor Receptor–Expressing Metastatic Colorectal Cancer Patients Treated With Single-Agent Cetuximab

Abstract: Our preliminary data suggest that these two polymorphisms may be useful molecular markers to predict clinical outcome in metastatic CRC patients treated with cetuximab and that they may indicate a role of ADCC of cetuximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
303
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(319 citation statements)
references
References 29 publications
9
303
7
Order By: Relevance
“…More importantly, "knobs-intoholes" mutations located in the CH3 domain did not affect antibody effector functions, which are mediated mainly by the CH2 domain of antibodies as evidenced by the high ADCC activity of Bi-Ab. ADCC is an important mechanism of action for therapeutic antibodies in vivo (47)(48)(49). The result from our ADCC assay demonstrates that Bi-Ab has comparable or slightly enhanced ADCC activity compared with monospecific antibodies, m590 and trastuzumab, and the Comb.…”
Section: Discussionmentioning
confidence: 77%
“…More importantly, "knobs-intoholes" mutations located in the CH3 domain did not affect antibody effector functions, which are mediated mainly by the CH2 domain of antibodies as evidenced by the high ADCC activity of Bi-Ab. ADCC is an important mechanism of action for therapeutic antibodies in vivo (47)(48)(49). The result from our ADCC assay demonstrates that Bi-Ab has comparable or slightly enhanced ADCC activity compared with monospecific antibodies, m590 and trastuzumab, and the Comb.…”
Section: Discussionmentioning
confidence: 77%
“…Several studies have documented specific anti-tumor IgGs directed against autologous host tumor cells, 84,85 yet the role of endogenous tumor reactive antibodies and their subsequent activation of innate immune cells by Fc/FcR interactions remains a question. 80 However, the observation that genetic polymorphisms in FcγRIIa and FcγRIIIa correlate with the clinical outcome of patients with B-cell lymphoma (rituximab), 4,86 colorectal cancer (cetuximab) 3,87 and breast cancer (trastuzumab) 5 implicate a role for antibody Fc/FcγR interactions in cancer immune surveillance, at least with anti-cancer mAb therapeutics. A more recent study indicated that anti-cancer mAb therapies can function to augment endogenous antibody responses to tumor surface antigens, in particular the antigen HER2.…”
Section: Discussionmentioning
confidence: 99%
“…This established that the ability of antibodies to reduce tumour burden was greatly reduced in the absence of immune cells expressing FcgRs. Secondly, colorectal, lymphoma and breast cancer patients carrying the polymorphic variants in the FcgRIIIa and FcgRIIa genes that encode for high affinity binding receptors for the Fc antibody segments, have the best clinical outcomes following antibody treatment (Weng and Levy, 2003;Zhang et al, 2007;Musolino et al, 2008).…”
mentioning
confidence: 99%